Be, V, and Cu in the halo star CS 31082-001 from near-UV spectroscopy. Issue 4 (3rd January 2022) - Ernandes, H; Barbuy, B; Friaça, A; Hill, V; Spite, M; Spite, F; Castilho, B V; Evans, C J
ABSTRACT: The 'First Stars' programme revealed the metal-poor halo star CS 31082-001 to be r-process and actinide rich, including the first measurement of a uranium abundance for an old star. To better characterize and understand such rare objects, we present the first abundance estimates of three elements (Be, V, Cu) for CS 31082-001 from analysis of its near-ultraviolet spectrum. Beryllium is rarely measured in giant stars, and we confirm that its abundance in this star is low due to the rather cool effective temperature that causes destruction of both Be and Li in its atmosphere. Vanadium and copper are iron-peak elements that are starting to be used as chemical-tagging indicators to investigate the origin of stellar populations. We find V and Cu abundances for CS 31082-001 that are comparable to other metal-poor stars, and present new chemical evolution models to investigate our results. In the case of V, extra nucleosynthesis due to interaction of neutrinos with matter is included in the models to be able to reproduce the measured abundance. Given the availability of high-quality spectroscopy of CS 31082-001, we also explore other atomic lines in the near-ultraviolet as a template for future studies of metal-poor stars with the planned CUBES instrument in development for the Very Large Telescope.